Automation of Two-Stage Factor VIII Assay - Stirling, Yvonne; Howarth, D J; Vickers, Marguerite; North, W R S; Meade, T W (Thrombosis and Haemostasis, 1978)
Two automated methods for two-stage factor VIII assays have been compared with one another, and evaluated in practice. The Depex method records the clotting time when an electric circuit is completed by the formation of a fibrin thread across a hook-type electrode; the Electra method is based on an optical density technique of clot detection. The two methods gave comparable results for measured levels of factor VIII when haemophilic or “normal” plasmas were assayed. Results from the two methods in practice also suggest that both are valid at low and “normal” factor VIII levels. The Electra method is also probably suitable for assays of concentrates; however, the Depex method appears to give falsely high values in these circumstances, and experimental findings suggest that the reason may be that increased viscosity due to the high fibrinogen levels in factor VIII concentrates causes premature closure of the circuit between the two ends of the Depex electrode. The main advantage of the Depex method is that, provided 3 or 4 machines are available, a given number of assays can be completed more quickly than on Electra. The main advantages of Electra are that it is probably subject to less laboratory error than Depex, and that it is suitable for assaying concentrates as well as haemophilic and “normal” plasmas.